2020
DOI: 10.22201/fmvz.24486760e.2020.4.837
|View full text |Cite
|
Sign up to set email alerts
|

Tumor prevalence in cats: experience from a reference diagnostic center in Mexico City (2006-2018)

Abstract: Records of referred cat cases received for diagnosis in the Department of Pathology of the National Autonomous University of Mexico, School of Veterinary Medicine and Animal Husbandry between 2006 and 2018, were reviewed to examine frequency of occurrence of neoplasms and associated demographic factors. To this end, the records of biopsies, necropsies and clinical information were analyzed to obtain data on animal sex and age, as well as neoplasm histotype, tissue of origin, and malignant/benign biological beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(60 reference statements)
0
4
0
1
Order By: Relevance
“…In domestic animals such as dogs, there is a high manifestation of tumors, probably because they are allowed to reach old age, as well as their close relationship with humans regarding the environment and food. The analysis of neoplasms in a population based on their histological origin and anaplastic behavior, in addition to their association with characteristics of the patient's data, can contribute to accurate diagnoses, and early and more appropriate treatments in daily practice 9,17,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In domestic animals such as dogs, there is a high manifestation of tumors, probably because they are allowed to reach old age, as well as their close relationship with humans regarding the environment and food. The analysis of neoplasms in a population based on their histological origin and anaplastic behavior, in addition to their association with characteristics of the patient's data, can contribute to accurate diagnoses, and early and more appropriate treatments in daily practice 9,17,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lymphomas were more frequently seen in male cats than female cats in another study (Dorn et al, 1968) but further research found that lymphomas had no significant correlation with sex (Shida et al, 2010). In addition, one study found that the median age of tumor incidence for cats was 9.5 years old (Pérez-Enriquez et al, 2020), while another reported a median of 9.14 years old (Rafalko et al, 2022;Pinello et al, 2022b). Further research found that tumors were most often detected between 6 and 14 years of age in cats (Pamukçu, 1954;MacEwen, 1990;Gülçubuk et al, 2005;Aydın et al, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Дані свідчать про те, що експресія цих білків змінюється в пухлинах і малігнізованих клітинних молочної залози, хоча ще не з'ясовано, чи є це причиною або наслідком неопластичного процесу [12]. Гормональні коливання, пов'язані з естральними циклами, впливають на розвиток пухлин молочних залоз [2,7,8,10,11,14]. Прогноз у більшості випадків неоплазій несприятливий, а смерть переважно пов'язана з місцевим рецидивом або метастазами.…”
Section: аналіз останніх досліджень і публікаційunclassified